2017
DOI: 10.1016/j.molimm.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

IL-17B: A new area of study in the IL-17 family

Abstract: The interleukin (IL)-17 superfamily, a relatively new family of cytokines, consists of six ligands (from IL-17A to IL-17F), which bind to five receptor subtypes (from IL-17RA to IL-17RE) and induce downstream signaling. IL-17A, a prototype member of this family, has been reported to be involved in the pathogenesis of allergies, autoimmune diseases, allograft transplantations, and malignancies. Unlike IL-17A, which is mainly produced by T helper 17 cells, IL-17B is widely expressed in various tissues. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…We found that a critical gene IL17RB was upregulated in catagen SHF compared with telogen SHF. IL17 superfamily is a relatively new family of cytokines, which consists of 6 ligands and can bind 5 receptor subtypes[ 21 ]. According to recent researches and our transcriptome data, we predicted that IL17RB might play a role in the development of SHF because it acts as a mediate signaling in many other physiological functions[ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that a critical gene IL17RB was upregulated in catagen SHF compared with telogen SHF. IL17 superfamily is a relatively new family of cytokines, which consists of 6 ligands and can bind 5 receptor subtypes[ 21 ]. According to recent researches and our transcriptome data, we predicted that IL17RB might play a role in the development of SHF because it acts as a mediate signaling in many other physiological functions[ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IL-17A represents the prototype member of the IL-17 cytokine family and is mainly produced by Th17 cells. Unlike IL-17A, IL-17B is widely expressed in various tissue types and its biological function is associated with pathologies, particularly to tumors ( 81 ).…”
Section: Cells Producing Il-17mentioning
confidence: 99%
“…It has been also observed that the signal triggered by the interaction of IL-17B with its receptor IL-17RB positively regulates Mesenchymal stem cells (MSCs) through the activation of the AKT/β-catenin pathway in gastric cancer. This suggests that IL-17B increases the progression of gastric cancer by the activation of MSCs ( 81 ).…”
Section: Cells Expressing Receptors For the Il-17 Familymentioning
confidence: 99%
“…The same study also showed that neutralization of IL-17B ameliorated disease. Relatively little is known regarding the role in RA of IL-17B, which has 29% homology with IL-17A (Bie et al, 2017). One study showed that IL-17B mRNA and protein is expressed in RA synovial tissue, where it is produced by neutrophils.…”
Section: Introductionmentioning
confidence: 99%